Inoculation of arbuscular mycorrhizal fungi on sugarcane varieties in the production of pre-sprouted seedlings - Lucas Aparecido Manzani Lisboa; Victor Gustavo Cunha Alves; Larissa Escalfi Tristão; Paulo Alexandre Monteiro de Figueiredo (Acta Biológica Catarinense, 2021)
Brazil is considered the largest producer of sugarcane in the world, the main raw material for the production of ethanol and sugar. The objective was to evaluate the effect of inoculation of arbuscular mycorrhizal fungi in sugarcane varieties in the production of pre-sprouted seedlings. An experiment was carried out in a completely randomized design, in a double factorial 4x2, with four varieties of cane: IACSP95-5000; IAC91-1099; IACSP95-5094 and IACSP97-4039 which interacted with and without the application of arbuscular mycorrhizal fungi on the substrate, with 20 repetitions, totaling 160 experimental units. The use of the mycorrhizal fungi cocktail provided changes in the initial development of the varieties IACSP97-4039, IACSP95-5094 and IACSP95-5000. The inoculation of arbuscular mycorrhizal fungi increased the parameters of the leaf area, the weight of the root dry matter, the adaxial epidermal thickness, the abaxial epidermal thickness, the phloem diameter and the mesophyll thickness.